Guidebook to Carbon Neutrality in China Macro and Industry Trends under New Constraints. (Springer Nature Singapore : Imprint: Springer, 2022)
This Open Access publication focuses on China's goal of achieving peak carbon emissions in 2030 and carbon neutrality by 2060. The book is the first to systematically build a framework combining a top-down and bottom-up analysis of this acute topic. What does carbon neutrality mean for economics in China? Might it imply stagflation or is it an opportunity to maximize the potential of green manufacturing? The book offers a comprehensive analysis of how the pursuit of carbon neutrality may influence the development of China's economy, and the country's biggest industries, while foreseeing the likely changes in people's lifestyles. In total, the book constructs a comprehensive path for China's carbon neutrality drive from the perspective of the green premium. This effort lays the foundation for a discussion of the country's emissions reduction plan. The book goes further, calculating the investment required for different sectors to achieve carbon neutrality, andillustrating the roles of carbon pricing and green finance in this undertaking. The book's information comes from a network of primary sources, including experts in the field and noted academics, to depict potential low-carbon roadmaps and green transitions in major industries. Emphasized is green development in sectors that will be critical to civilization, including in technology, energy, manufacturing, transportation, and urban planning, which are backed by in-depth discussions and analyses. Accessible and academically rigorous, the work is anchored in the economics of carbon neutrality, extends to potential policy implications and identifies investment opportunities. This valuable reference will attract readers interested in public policy, economics, finance, and investors who seek to better understand China's prospects in the low-carbon economy of the near future.